Penerapan Kombinasi Model Pembelajaran Tipe Numbered Head Together (NHT) dengan Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Bahasa Indonesia Kelas IV SDN Pegirian II/495 Surabaya - Nadya Nur Aini; Wiryanto Wiryanto; Nency Putri Muldash (Departement of Mathematics Education, 2023)
This study aims to determine the success of the combination of the numbered head together (nht) type learning model with the problem based learning model to improve Indonesian learning outcomes for class IV SDN Pegirian II/495 Surabaya. Classroom action research with the steps of planning, implementing, observing, and reflecting. The research results were obtained from observations from cycle I and cycle II. Based on class action research activities, the percentage of classical completeness cycle I was 70.58% with an average score of 61.76 and an increase in the implementation of cycle II was 82.35% with an average score of 81.47. The results of the percentage of activeness in the first cycle were 62.74 in the moderately active category and an increase in cycle II was 89.86 in the very active category. Based on these results it can be concluded that the application of a combination of a numbered head together type learning models with problem based learning in class IV students can improve the ability to write paragraphs using conjunction sentences at SDN Pegirian II/495, Surabaya City.